Sistem Pakar Dalam Penentuan Mustahiq Zakat Menggunakan Dempster Shafer - Feri Setiawan; Ahmadi Irmansyah Lubis (Forum Kerjasama Pendidikan Tinggi, 2022)
Zakat is one of the obligations for a Muslim and is one of the five pillars of Islam. In the zakat system, it consists of two elements, namely Mustahiq (who has the right to receive zakat) and Muzakki (who has the right to pay zakat). Based on interviews conducted by the author with the Amil Zakat Infaq Shadaqoh Muhammadiyah Institute (LAZISMU) Sunggal District, Deli Serdang Regency, lies are often found because the system used is still manual in identifying the eligibility of zakat mustahiq, most of which are falsification of income data and data that have received assistance. This causes the distribution of zakat to be uneven. This study builds a system that can provide knowledge to the public, especially Muslims, about mustahiq zakat and its criteria. In the study, the development of an intelligent system that is able to identify mustahiq zakat which is computed into an Android-based application which will then be used globally by the community to identify whether a person is included or not included as mustahiq zakat. As for building the application in this study, the Dempster Shafer method based on the Expert System is used in order to produce an output that can be right on target in accordance with the expected target. The results of the study used 11 criteria, 8 asnaf and 12 rule based. The results obtained from the system testing carried out can be said that the system that has been built is able to assist in the process of systematically identifying zakat mustahiq with the expected system output